Incubating Graduate Entrepreneurs in Kenya: Nested Case Studies of Kenyatta University Chandaria Business Innovation Incubation Centre - Nyerere, Jackline; Opinde, Godwin; Muthoni, Purity; Mutuma, Wilson (Papers in Education and Development, 2022)
Abstract High unemployment rate in Kenya has contributed to policy focus on entrepreneurship. In response, universities have incorporated entrepreneurship in their curricula albeit, to a lesser extent, through incubation of social entrepreneurs. The objective of this study was to demonstrate how social entrepreneurship skills are nurtured through incubation centers. A nested case study research approach was used to select relevant social entrepreneurship projects incubated at Kenyatta University ' s Chandaria Business Innovation Incubation Centre (KUCBIIC). The study involved literature review and in-depth interviews with KUCBIIC staff, entrepreneurs, staff and clients of selected incubation projects. Findings indicated that the incubation hub has enabled development of ideas into unique products which not only contribute towards employment but also provide solutions to various societal challenges. Keywords: entrepreneurship education, incubation, innovation